Control of Calcium Oxalate Morphology Through Electrocrystallization as an Electrochemical Approach for Preventing Pathological Disease - Silva-Rojas, J; Silva-Rojas, J (Institute for Ionics, 2015)
Pathological crystallization of calcium oxalate (CaOx) inside the urinary tract is called calculi or kidney stone (Urolithiasis). CaOx exhibits three crystalline types in nature: CaOx monohydrate COM, dihydrate COD and trihydrate COT. COD and COM are often found in urinary calculi, particularly COM. Electrocrystallization has been recently used to perform oriented crystallization of inorganic compounds such as Ca-salts. Although many mineralization methods exist, the mechanisms involved in the control of CaOx polymorphism still remain unclear. Herein, we induced selective electrocrystallization of COD by modifying the electrical current, time and electrochemical cell type. By combining above factors, we established an efficient method without the use of additives for stabilizing non-pathological CaOx crystals. We found notorious stabilization of CaOx polymorphisms with hierarchically complex shape with nano-organization assembly, size and aggregated crystalline particles. Our results demonstrated that, by using an optimized electrochemical approach, this technique could have great potential for studying the nucleation and crystal growth of CaOx through functionalized synthetic polymers, and to develop a novel pathway to evaluate new calculi preventing-compound inhibitors. [Figure not available: see fulltext.] © 2015, Springer-Verlag Berlin Heidelberg.